2016
DOI: 10.1016/j.jmii.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of aminoglycosides against clinical isolates of Acinetobacter baumannii complex and other nonfermentative Gram-negative bacilli causing healthcare-associated bloodstream infections in Taiwan

Abstract: Background/Purpose: Aminoglycosides possess in vitro activity against aerobic and facultative Gram-negative bacilli. However, nationwide surveillance on susceptibility data of Acinetobacter baumannii complex and Pseudomonas aeruginosa to aminoglycosides was limited, and aminoglycoside resistance has emerged in the past decade. We study the in vitro susceptibility of A. baumannii complex and other nonfermentative Gram-negative bacilli (NFGNB) to aminoglycosides. Methods: A total of 378 NFGNB blood isolates caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…Our study revealed that colistin (92%) and gentamicin (85%) were the most active antibiotics, whereas, in earlier studies, the results of the spectrum rates of colistin (60%) and trimethoprim and sulfamethoxazole (46%) did not correlate with our studies [ 43 , 44 ]. Among the clinical isolates, A. baumannii was extremely resistant to two carbapenem drugs, meropenem (57%) and imipenem (53%), and these spectrum rates were not correlated with previous studies [ 45 ], indicating that the spectrum of the antimicrobial resistance profile may vary from place to place and nosocomial-associated pathogens.…”
Section: Discussioncontrasting
confidence: 97%
“…Our study revealed that colistin (92%) and gentamicin (85%) were the most active antibiotics, whereas, in earlier studies, the results of the spectrum rates of colistin (60%) and trimethoprim and sulfamethoxazole (46%) did not correlate with our studies [ 43 , 44 ]. Among the clinical isolates, A. baumannii was extremely resistant to two carbapenem drugs, meropenem (57%) and imipenem (53%), and these spectrum rates were not correlated with previous studies [ 45 ], indicating that the spectrum of the antimicrobial resistance profile may vary from place to place and nosocomial-associated pathogens.…”
Section: Discussioncontrasting
confidence: 97%
“…5 Pseudomonas aeruginosa is found to be less sensitive to amikacin (41.60%) and gentamycin (45.80%) as compared to another study conducted at Taiwan in which resistance for amikacin and gentamycin was 98% an 94% respectively. 6 There are few different mechanisms involved in drug resistance of Pseudomonas.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its involvement in cell wall breakage and leakage of cell components as shown here may be indirect. Gen is reported to be associated with the cell death process because it interferes with protein synthesis and caused internal cellular damage, subsequently causing cell rupturing 24 , which then lead to the release of intracellular components of the cell into the medium.
Figure 2 Effect of different concentrations of tested drugs on selected cell physiological function indices to determine cell leakage and ATP synthase loss; ( A ) intracellular protein leakage; ( B ) DNA leakage; ( C ) ATP synthase loss; ( D ) potassium ion leakage.
…”
Section: Resultsmentioning
confidence: 99%